A three-dimensional porous catalyst for synergistically controlling chlorobenzene and mercury and a preparation method thereof

The three-dimensional porous CuO modified CeO2-Al2O3 catalyst prepared by the dual-template method solves the problems of catalyst deactivation and secondary pollution in the catalytic oxidation method, and achieves efficient synergistic catalytic oxidation of chlorobenzene and mercury, which improves the stability of the catalyst and chlorine toxicity.

CN116159567BActive Publication Date: 2024-12-20XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310164649.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-25
Publication Date
2024-12-20
Estimated Expiration
2043-02-25

AI Technical Summary

Technical Problem

The existing catalytic oxidation methods are prone to catalyst deactivation and secondary contamination problems when treating chlorobenzene and mercury, making it difficult to achieve effective coordinated control of chlorobenzene and mercury.

Method used

The CuO modified CeO2-Al2O3 catalyst with three-dimensional porous structure was prepared by the dual-template method. The catalyst with large pore and mesoporous structure was formed by PMMA as the hard template and F127 as the soft template, thereby improving the oxidation activity and anti-chlorine poisoning of the catalyst. .

Benefits of technology

It significantly improves the stability and catalytic properties of the catalyst, promotes the deep oxidation of chlorobenzene and mercury, reduces the deposition of polychlorinated by-products, and enhances the catalyst's anti-chlorination poisoning ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116159567B_ABST
    Figure CN116159567B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for synergistically controlling chlorobenzene (CB) and mercury (Hg 0 ) and a preparation method thereof, wherein the three-dimensional porous catalyst is composed of a composite metal oxide of transition metal CuO modified CeO2‑Al2O3. The catalyst is prepared by a dual template method (PMMA is a hard template and F127 is a soft template), Cu(NO3)2·3H2O, Ce(NO3)3·6H2O, and Al(NO3)3·9H2O are metal sources, Al2O3 accounts for 4-6% of the total mass of the catalyst, the doping amount of CuO is 10-25%, and the balance is CeO2. The catalyst prepared by the present invention has both macroporous and mesoporous structures, can efficiently and synergistically catalyze the oxidation of chlorobenzene and mercury, promote the good dispersion of surface active components and the exposure of active sites, effectively inhibit the deposition of surface chlorine species, and improve the stability of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of porous composite metal oxide catalysts, and in particular relates to a three-dimensional porous catalyst for synergistically controlling chlorobenzene and mercury and a preparation method thereof. Background Art

[0002] Chlorobenzene (CB) is an important precursor to dioxins and a typical chlorinated volatile organic compound (CVOCs). It has attracted much attention due to its high chemical stability and strong toxicity. In order to make the emissions of chlorobenzene and mercury meet the new national environmental protection emission standards, it is urgent to adopt end-of-pipe treatment to control the emissions of pollutants. Therefore, it is urgent to formulate relevant standards, develop advanced technologies, and coordinate the control of such persistent pollutants.

[0003] Chlorobenzene and mercury are usually adsorbed by activated carbon, but the cost is too high and it can only convert dioxins from gas phase to solid phase, but cannot fundamentally destroy and decompose dioxins. The residual waste containing mercury and dioxins produced later has secondary pollution problems. How to deal with these growing solid residues from incineration has become a difficult problem. Catalytic oxidation is considered to be a promising end-of-pipe treatment technology due to its low energy consumption, high purification degree, and low secondary pollution, especially for low-concentration organic compounds. It can convert Hg 0 Converted to Hg 2+ At the same time, chlorobenzene is oxidized into small molecules such as CO2, H2O, and HCl.

[0004] However, chlorine poisoning and catalyst deactivation caused by secondary pollution are still the key factors restricting the widespread application of this technology in industry. In order to solve this problem, chlorine species are further converted into small molecule inorganic substances such as HCl and Cl2, which can quickly react with Hg 0 There are currently three main strategies to improve the performance of synergistic catalytic oxidation of chlorobenzene and mercury, namely, constructing a three-dimensional porous structure, enhancing oxidation capacity, and increasing acid sites. Three-dimensional porous catalysts can well disperse active components with high porosity, improve the adsorption and diffusion capacity of reactants through highly exposed active surfaces, promote the deep oxidation of intermediates accumulated on the catalyst surface, and show excellent oxidation activity and resistance to chlorine poisoning against VOCs and mercury.

[0005] CuO has excellent coordination flexibility and rich redox properties, making it an ideal oxide for oxidation-type catalysts. Adding CuO to CeO2 will produce lattice defects, leading to the formation of more oxygen vacancies, which helps to improve the adsorption activation of oxygen molecules and oxygen mobility, and increase the CB and Hg 0 In addition, due to the electron transfer between CuO and CeO2, the synergistic effect of acid and redox sites can be enhanced, which can further benefit Hg 0Oxidation. In addition to the redox ability, more acid sites also play a positive role in the degradation of CVOCs molecules. Among them The acid can provide a proton H + , promote the cleavage of the C-Cl bond, and promote the formation of HCl. The strength of the Lewis acid determines the redox performance of the catalyst, which can promote the deep oxidation of intermediate products, thereby improving the selectivity of CO2. It can be inferred that the preparation of a CuO-modified CeO2-Al2O3 catalyst with a three-dimensional porous structure for the synergistic catalytic oxidation of CB and Hg 0 is very promising. SUMMARY OF THE INVENTION

[0006] Aiming at the technical problems such as catalyst deactivation caused by chlorine poisoning and secondary pollution when treating chlorobenzene, mercury and dioxin by the above catalytic oxidation method, the present invention provides a three-dimensional porous catalyst for the synergistic control of chlorobenzene (CB) and mercury (Hg 0 ), and a preparation method thereof. The catalyst is prepared by a double-template method (PMMA as the hard template and F127 as the soft template).

[0007] In order to achieve the above object, the technical solution provided by the present invention is as follows:

[0008] A three-dimensional porous catalyst for the synergistic control of chlorobenzene and mercury, which is composed of a composite oxide of CeO2-Al2O3 and transition metal CuO-modified CeO2-Al2O3. The porous catalyst is denoted as Cu x CeAl, where x is the percentage of CuO in the total mass of the catalyst, 0 < x ≤ 25%, preferably 10% ≤ x ≤ 25%.

[0009] Further, the porous catalyst is composed of the following components in mass percentage:

[0010] Al2O3 4% - 6% (more preferably 5%), CuO 10% - 25%, and the balance is CeO2. The sum of the mass percentages of each component is 100%.

[0011] Further, the porous catalyst has a rich macroporous and mesoporous structure, with a specific surface area of 80 - 480 m 2 / g, a total pore volume of 0.1 - 0.9 cm 3 / g, and an average pore diameter of 6 - 8 nm.

[0012] The preparation method of the above three-dimensional porous catalyst for the synergistic control of chlorobenzene and mercury includes the following steps:

[0013] (1) Synthesize a PMMA emulsion by the soap-free emulsion polymerization method, and obtain a PMMA colloidal crystal hard template by self-assembly of solvent evaporation through the constant-temperature suspension film-forming method;

[0014] (2) Using surfactant F127 as a soft template, mixing it with a metal precursor solution to form micelles, and forming mesopores through intermolecular forces to obtain an F127-assisted metal precursor solution;

[0015] (3) pouring the F127-assisted metal precursor solution obtained in step (2) onto the PMMA colloidal crystal hard template obtained in step (1) to fill the voids of the PMMA microspheres, and finally burning the PMMA microspheres by heat treatment to form a composite metal oxide with a macroporous structure and mesoporous walls, i.e., a three-dimensional porous catalyst.

[0016] Furthermore, in step (1), the preparation method of the PMMA colloidal crystal hard template is specifically as follows: 1-1.2 mol of methyl methacrylate (MMA) is added to 70-80 mol of deionized water and stirred evenly, the polymerization reaction is carried out under anaerobic conditions at 70±1°C, nitrogen is passed throughout the reaction process, 1-2 mmol of potassium persulfate initiator is added, the emulsification time is 40-50 min, after the reaction, it is poured into cold deionized water and diluted 1-2 times, the polymerization reaction is terminated, and a polymethyl methacrylate emulsion is prepared, the emulsion is centrifuged at a speed of 3000-5000 rpm for 30-60 min, the precipitate is taken, and the deionized water is added to dilute 30-100 times, ultrasonic dispersion is performed, and constant temperature evaporation is performed at 80-90°C to make it self-assemble to form an ordered PMMA colloidal crystal hard template.

[0017] Furthermore, step (2) is specifically as follows: F127 and ethanol solution are mixed at 20-25° C. to form a solution with a concentration of 0.1-0.2 g / mL, stirred until completely dissolved to form a uniform solution, and then the metal precursor solution is added, and stirred continuously until completely dissolved, clarified, and a sol-like state appears.

[0018] Furthermore, the ethanol solution is an ethanol solution obtained by mixing 1-3 parts by mass of H2O and 17-19 parts by mass of anhydrous ethanol; the metal precursor solution is a mixed solution obtained by dissolving copper nitrate Cu(NO3)2·3H2O, cerium nitrate Ce(NO3)3·6H2O and aluminum nitrate Al(NO3)3·9H2O in a molar ratio of (1-4):(4-8):(1-2), and the total metal ion concentration is 0.1-1 mol / L.

[0019] Furthermore, step (3) is specifically as follows: pouring the F127-assisted metal precursor solution on the PMMA template, and after completely soaking it (sufficiently filling the gaps of the PMMA microspheres), placing it in a vacuum drying oven and aging it at vacuum room temperature for 12 to 18 hours, taking it out and rinsing it with ethanol solution, filtering the excess solution with a Buchner funnel, placing the filter cake in a 40 to 50 ° C oven and drying it for 12 to 18 hours, placing the dried solid in a muffle furnace and calcining it, raising the temperature from room temperature to 250 to 350 ° C at a rate of 1 to 2 ° C / min and maintaining it for 2 to 3 hours, then raising it to 450 to 550 ° C and maintaining it for 2 to 3 hours, and then cooling it to room temperature to obtain a three-dimensional porous catalyst.

[0020] The present invention will be further described below:

[0021] The present invention adopts a dual template method to synthesize a series of three-dimensional porous CuO modified CeO2-Al2O3 catalysts with good pore structure and high specific surface area for the synergistic catalytic oxidation of CB and Hg 0 The presence of appropriate CuO can introduce more Cu and Ce ions into the cerium lattice in the form of Cu-O-Ce solid solution and induce the formation of structural defects and a large number of oxygen vacancies, resulting in higher active oxygen concentration and better active oxygen mobility, which is crucial for the deep oxidation of chlorinated intermediates. The electronic induction effect between CuO and CeO2 is very important for improving the CB and Hg 0 In addition, the macroporous framework and mesoporous nanostructure significantly increase the specific surface area, thereby improving the contact efficiency between reactants and active sites, thereby significantly reducing the deposition of polychlorinated byproducts. It can be speculated that these CuO-modified CeO2-Al2O3 catalysts with three-dimensional porous structures have a positive effect on the catalytic oxidation of CB and Hg 0 This may be an effective way to develop new catalysts with chlorine resistance.

[0022] The technical effects of the present invention are:

[0023] The catalyst prepared by the present invention has both macroporous and mesoporous structures, can efficiently and synergistically catalyze the oxidation of chlorobenzene and mercury, promote good dispersion of surface active components and exposure of active sites, effectively inhibit the deposition of surface chlorine species, and improve catalyst stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The three-dimensional porous Cu prepared in Example 3 20 Flow chart of the preparation of CeAl catalyst.

[0025] Figure 2 The three-dimensional porous Cu prepared in Example 3 20 Scanning electron microscopy image of CeAl catalyst.

[0026] Figure 3 The three-dimensional porous Cu prepared in Example 3 20 Adsorption / desorption curves of CeAl catalyst.

[0027] Figure 4 The three-dimensional porous Cu prepared in Example 3 20 Pore ​​size distribution of CeAl catalyst. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below with reference to specific embodiments, but the present invention is not limited thereto.

[0029] Example 1

[0030] 1.08 mol of methyl methacrylate (MMA) was added to 72.16 mol of deionized water and stirred evenly. The polymerization reaction was carried out under anaerobic conditions. After stirring for 15 minutes in a 70°C water bath, 1.48 mmol of potassium persulfate initiator was added to react for 45 minutes. After the reaction, the emulsion was quickly poured into 1500 mL of cold deionized water to terminate the polymerization reaction. After the emulsion was centrifuged at 4000 rpm for 50 minutes, the precipitate was diluted 100 times with deionized water, and after ultrasonic dispersion for 30 minutes, the solution was heated in a 80°C water bath until the water in the emulsion was completely evaporated to obtain an ordered PMMA colloidal crystal hard template.

[0031] Example 2

[0032] The synergistic control of CB and Hg 0 The preparation method of the three-dimensional porous CeO2-Al2O3 catalyst comprises the following steps:

[0033] (1) Dissolve 1 g of F127 in 10 mL of 95% ethanol solution at 25°C in a water bath.

[0034] (2) adding 3.6871 g Ce(NO3)3·6H2O and 0.5660 g Al(NO3)3·9H2O to the solution obtained in step (1) in sequence under stirring, and stirring for 6 h until the solution becomes clear and in a sol-like state;

[0035] (3) pouring the mixed solution obtained in step (2) onto 3 g of dried PMMA microspheres, and placing them in a vacuum drying oven for aging at room temperature under vacuum for 18 h after they are completely soaked;

[0036] (4) After taking out, rinse with 95 wt% ethanol solution, filter the excess solution with a Buchner funnel, and dry the solid in an oven at 50°C for 18 h;

[0037] (5) The catalyst was placed in a muffle furnace and calcined at a rate of 1°C / min from room temperature to 300°C and maintained for 2 h, then raised to 500°C and maintained for 3 h, and then cooled to room temperature to obtain a porous CeO2-Al2O3 catalyst.

[0038] Example 3

[0039] The synergistic control of CB and Hg 0 The preparation method of the three-dimensional porous CuO / CeO2-Al2O3 catalyst comprises the following steps:

[0040] (1) Dissolve 1 g of F127 in 10 mL of 95% ethanol solution in a 25°C water bath.

[0041] (2) adding 0.7735 g Cu(NO3)2·3H2O, 2.4096 g Ce(NO3)3·6H2O and 0.4685 g Al(NO3)3·9H2O to the solution obtained in step (1) in sequence under stirring, and stirring for 6 h until the solution becomes clear and in a sol-like state;

[0042] (3) pouring the mixed solution obtained in step (2) onto 3 g of dried PMMA microspheres, and placing them in a vacuum drying oven for aging at room temperature under vacuum for 18 h after they are completely soaked;

[0043] (4) After taking out, rinse with 95 wt% ethanol solution, filter the excess solution with a Buchner funnel, and dry the solid in an oven at 50°C for 18 h;

[0044] (5) The catalyst was placed in a muffle furnace and calcined at a rate of 1°C / min from room temperature to 300°C and maintained for 2 h, then raised to 500°C and maintained for 3 h, and then cooled to room temperature to obtain a porous CuO / CeO2-Al2O3 catalyst.

[0045] Example 4

[0046] The three-dimensional porous CuO / CeO2-Al2O3 catalyst of the present invention synergistically controls CB and Hg 0 Performance test of coordinated control of CB and Hg in a fixed bed reactor 0 Activity test. The catalyst in Example 3 was loaded into a catalytic reactor, and the simulated flue gas of the gas distribution system consisted of 10 vol.% O2, 200 ppm SO2, 100 ug / m 3 Hg 0 , 100ppm CB and balance gas N2, the total gas flow rate was maintained at 200mL / min, and the volume space velocity (GHSV) was 40 000h -1 The reaction temperature was controlled in the range of 100-400°C to test the synergistic catalytic oxidation of CB and Hg 0 conversion efficiency.

[0047] Example 5

[0048] BET and SEM tests of the catalyst of the present invention

[0049] The specific surface area and pore structure analysis of all catalysts in the present invention are carried out by N2 physical adsorption experiment using the automatic gas adsorption system of Quantachrome NOVA-2200e of Quantachrom Instruments (USA), and the specific surface area, total pore volume and pore size distribution of the catalyst are measured. After taking 0.1g sample and degassing at 180℃ for 5h, N2 is used as adsorbent and the experimental measurement is carried out at a temperature of 77K. According to the Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) methods, the specific surface area, total pore volume and average pore size are obtained. In addition, the scanning electron microscope (SEM) analysis of all catalysts in the present invention is taken by Hitachi JEOL JSM-6360LV electron scanning microscope.

[0050] The results show that the three-dimensional porous catalyst in the present invention has a large specific surface area and pore volume. The unique pore structure can increase the contact area between the reaction molecules and the active sites of the catalyst, thereby accelerating the reaction of CB and Hg 0 The deep oxidation reduces the accumulation of polychlorinated byproducts and further effectively exposes more active sites.

Claims

1. A three-dimensional porous catalyst for synergistically controlling chlorobenzene and mercury, characterized in that: The porous catalyst is composed of a composite oxide of CeO2-Al2O3 modified by transition metal CuO. The porous catalyst is denoted as Cu x CeAl, where x is the percentage of CuO in the total mass of the catalyst, 0 <x≤25%; The porous catalyst is composed of the following components in percentage by weight: composition: Al2O3 4%~6%, CuO 10%~25%, the balance is CeO2, the sum of the mass percentages of each component is 100%; The porous catalyst has abundant macropores and mesopores, and the specific surface area is 80-480 m 2 / g, with a total pore volume of 0.1-0.9 cm 3 / g, and the average pore size is 6~8 nm.

2. The method for preparing the three-dimensional porous catalyst for synergistically controlling chlorobenzene and mercury according to claim 1, characterized in that: The steps include: (1) PMMA emulsion was synthesized by soap-free emulsion polymerization, and the PMMA colloidal crystal hard template was obtained by self-assembly through solvent evaporation by constant temperature suspension film formation method; (2) Using surfactant F127 as a soft template, it is mixed with a metal precursor solution to form micelles, and mesopores are formed through intermolecular forces to obtain an F127-assisted metal precursor solution; (3) pouring the F127-assisted metal precursor solution obtained in step (2) onto the PMMA colloidal crystal hard template obtained in step (1) to fill the voids of the PMMA microspheres, and finally burning the PMMA microspheres by heat treatment to form a composite metal oxide with a macroporous structure and mesoporous walls, i.e., a three-dimensional porous catalyst.

3. The preparation method according to claim 2, characterized in that: In step (1), the preparation method of the PMMA colloidal crystal hard template is specifically as follows: 1-1.2 mol of methyl methacrylate is added to 70-80 mol of deionized water and stirred evenly, the polymerization reaction is carried out under anaerobic conditions at 70±1 °C, nitrogen is passed throughout the reaction process, 1-2 mmol of potassium persulfate initiator is added, the emulsification time is 40-50 min, after the reaction, it is poured into cold deionized water and diluted 1-2 times, the polymerization reaction is terminated, and a polymethyl methacrylate emulsion is prepared, the emulsion is centrifuged at 3000-5000 rpm for 30-60 min, the precipitate is taken and diluted 30-100 times with deionized water, ultrasonically dispersed, and evaporated at a constant temperature of 80-90 °C to make it self-assemble to form an ordered PMMA colloidal crystal hard template.

4. The preparation method according to claim 2, characterized in that: Step (2) is specifically as follows: F127 and ethanol solution are mixed at 20-25 °C to form a solution with a concentration of 0.1-0.2 g / mL, stirred until completely dissolved to form a uniform solution, and then the metal precursor solution is added, and stirred continuously until completely dissolved, clarified, and a sol-like state appears.

5. The preparation method according to claim 4, characterized in that: The ethanol solution is an ethanol solution obtained by mixing 1-3 parts by mass of H2O and 17-19 parts by mass of anhydrous ethanol; the metal precursor solution is a mixed solution obtained by dissolving copper nitrate Cu(NO3)2·3H2O, cerium nitrate Ce(NO3)3·6H2O and aluminum nitrate Al(NO3)3·9H2O in a molar ratio of (1~4): (4~8): (1~2), and the total metal ion concentration is 0.1~1 mol / L.

6. The preparation method according to claim 2, characterized in that: Step (3) is specifically as follows: pouring the F127-assisted metal precursor solution on the PMMA template, and after completely soaking it, placing it in a vacuum drying oven and aging it at vacuum room temperature for 12 to 18 hours, taking it out and rinsing it with ethanol solution, filtering the excess solution with a Buchner funnel, placing the filter cake in a 40 to 50 °C oven and drying it for 12 to 18 hours, placing the dried solid in a muffle furnace and calcining it at a rate of 1 to 2 °C / min from room temperature to 250 to 350 °C and maintaining it for 2 to 3 hours, then raising it to 450 to 550 °C and maintaining it for 2 to 3 hours, and then cooling it to room temperature to obtain a three-dimensional porous catalyst.